PENGEMBANGAN BUKU AJAR AKUNTANSI PERPAJAKAN BERBASIS MASALAH - Edutivia Mardetini; Dian Eka Amrina; Sani Safitri (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2020)
The research problems is how the validity and effectiveness of tax accounting textbooks based on problem based learning. As for the purpose of this study is to describe the level of validity and effectiveness of tax accounting textbooks based on problem based learning. This type of research is a R&D research by Borg & Gall. The population in this study were all students of economic education in the even semester of the 2019-2020 academic year. With the research sample, namely students who took the tax accounting course at Indralaya class, totaling 56 students. The data collection techniques used were documentation, questionnaires, and tests. With a test of validity result is 3.40 from material experts categorized as very valid and 3.19 from media experts who are categorized as valid. Then from the effectiveness test, the textbook effectiveness value obtained a gain of 0.38 which is included in the moderate/effective category. Thus, the development of tax accounting textbooks based on problem based learning is valid and effective for use in lecture activities.